Leveraging the postpartum period to reduce racial disparities in postpartum hypertension care - Malamo E. Countouris; Jared W. Magnani (American Heart Journal Plus)
Pregnancy provides a window of opportunity for management of hypertension care. Particularly in the postpartum period – the so-called “4th trimester” – individuals of Black race are at increased risk for hypertension-related morbidity and mortality. Telehealth interventions, such as remote blood pressure monitoring programs and virtual postpartum visits, can reduce racial disparities in the delivery of recommended care. System and policy changes can address social factors that impact postpartum care as well. Cardiovascular clinicians have a key role to play in managing hypertension and addressing cardiovascular disease prevention strategies during reproductive years.